Like a Pelican in the Wilderness: Reflections on the Sayings of the Desert Fathers. - Ramfos, Stelios (Brookline Holy Cross Orthodox Press, 1994)
Like a Pelacan in the Wilderness is a dialogue with the teachings of the desert fathers, to see what light they can shed on some of the central theological issues of today. These issues are to do with the meaning of eschatological time, with what it is to live in the perspective of the telos, with how transparency and opennes are to be attained, with the nature of personhood as the goal of human existence. Antony, Macarius, Arsenius and many others went into the desert to strip themselves down to the essential core of their being so that they could be transformed by God. Even if we cannot imitate them, they have much to teach us.
Keywords: Fiction